2023
DOI: 10.3390/diagnostics13061100
|View full text |Cite
|
Sign up to set email alerts
|

YOLOv5s-SA: Light-Weighted and Improved YOLOv5s for Sperm Detection

Abstract: Sperm detection performance is particularly critical for sperm motility tracking. However, there are a large number of non-sperm objects, sperm occlusion and poorly detailed texture features in semen images, which directly affect the accuracy of sperm detection. To solve the problem of false detection and missed detection in sperm detection, a multi-sperm target detection model, Yolov5s-SA, with an SA attention mechanism is proposed based on the YOLOv5s algorithm. Firstly, a depthwise, separable convolution st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In the future, we will also compare this proposed SqueezeNet-Light architecture with other recently developed lightweight [49,50] architectures to confirm the generalizability of the network.…”
Section: Discussionmentioning
confidence: 98%
“…In the future, we will also compare this proposed SqueezeNet-Light architecture with other recently developed lightweight [49,50] architectures to confirm the generalizability of the network.…”
Section: Discussionmentioning
confidence: 98%
“…These preprocessing tasks aim to perform encoding checks, remove non-alphanumeric characters, clean digits, normalize whitespace, convert case, tokenize, and stem words. Additionally, we utilized three machine learning methods from the sklearn library-Support Vector Machine (SVM) [35], Logistic Regression (LR) [36], and Random Forest (RF) [37]-for comparative analysis of algorithm performance.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…Li et al [38] proposed an MTC-YOLOv5 algorithm for the detection of cucumber plant diseases, which added Coordinate attention (CA) to reduce background interference, combined a Multi-scale (MS) training to improve the detection accuracy of small targets, and experimental results showed that the algorithm had high detection accuracy and speed. Zhu et al developed a faster and more accurate SE-YOLOV5 model [39] proposed an improved YOLOv5 model for fast sperm detection, which added a Shuffle attention (SA) mechanism to enhance the detection performance of sperm and used DWConv to enhance the speed of convergence. Experiments showed that the model effectively reduced sperm leakage and improved detection accuracy.…”
Section: Related Workmentioning
confidence: 99%